Isu Kewarganegaraan Kontemporer Di Indonesia: Radikalisme, Intoleransi, Korupsi, Dan Disintegrasi Bangsa - Suwisty Ratu, Monica (JPT : Jurnal Pendidikan Tematik, 2025)
We are currently living in an era that must be addressed seriously. Many questions arise regarding "What are the current citizenship issues?" And it turns out that there are interconnected influences within them, the resulting impact of which can change our lives as a nation. From this perspective, this article was written to explore more broadly how the influence of current issues can be considered destructive to a nation's identity. And how can we instill national values ​​amidst the onslaught of global values? This research applies a descriptive qualitative study method through scientific sources based on up-to-date information to adapt to the current social context.